Duration of maternal mental health-related outcomes after an infant’s death: A retrospective matched-cohort study using linkable administrative data - Elizabeth Wall-Wieler; Leslie Roos; James Bolton (International Journal of Population Data Science, 2018)
Introduction Mothers have increased mental illness such as anxiety and depression after the death of a child.